Comparative Seismic Analysis Of An Irregular Building With A Shear Wall And Frame Tube System Of Various Sizes (International Journal of Engineering and Computer Science, 2017)
Lateral load effects on high rise buildings are quite significant and increase rapidly with increase in height. In high rise structures, the behavior of the structure is greatly influenced by the type of lateral system provided and the selection of appropriate. The selection is dependent on many aspects such as structural behavior of the system economic feasibility and availability of materials. Few of the lateral structural systems are Shear wall system, Braced frame system, Framed tube system, Tube in tube system, Bundled tube system. The lateral structural systems give the structure the stiffness, which would considerably decrease the lateral displacements. In the present work a Plain frame system, a Shear wall system and Framed tube system are considered for 30, 40, 50 and 60 story structures. The analysis has been carried out using software Etabs The roof displacements, internal forces (Support Reactions, Bending Moments and Shear Forced) of members and joint displacements are studied and compared. It is seen that the Shear wall system is very much effective in resisting lateral loads for the structures up to 30 stories and for structures beyond 30 stories the Framed tube system is very much effective than Shear wall system in resisting lateral loads.